(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2024)
This study investigates the efficacy of transitioning from TLE (Tenofovir/Lamivudine/Efavirenz) to TLD (Tenofovir/ Lamivudine/ Dolutegravir) as a first-line antiretroviral therapy for the management of HIV. A retrospective analysis was conducted involving 261 individuals in whom 145 patients were initially treated with TLE in 2017 who were transitioned to TLD in 2020 and 116 patients given TLD as first-line therapy from 2020 onwards. Clinical parameters like Viral load (VL), CD4 cell count, and WHO clinical stage were evaluated at baseline to study the effectiveness of the treatment. In addition, the non-clinical variables like age, sex, weight, mode of transmission and body mass index (BMI) were analyzed. The results signified enhancements in CD4 count, viral load and weight across both groups (TLE to TLD transition and TLD initiated as first-line therapy) with a statistical significance of P<0.001***. The median BMI for patients transitioning from TLE to TLD was 21.63 (IQR 19.62-24.37) with a p-value of 0.004**, while the median BMI for patients on TLD as a first-line therapy was 20.83 (IQR 18.95-23.87), exhibiting a p-value of 0.115ns indicating no substantial difference between both groups. The findings showed effective viral suppression, with viral loads categorized as Target Not Detected (TND) and CD4 counts exceeding 500 cells/mm3. Overall, the integration of TLD into ART regimen resulted in improved clinical outcomes and sustained viral suppression among the patients showing the advantage of this therapeutic transition in HIV management.